In vitro antibacterial activities of Broccoli (Brassica oleracea L.var italica) against food borne bacteria - Sibi G, Abhilasha Shukla, K. Dhananjaya, K.R. Ravikumar and H. Mallesha (Journal of Applied Pharmaceutical Science, 2013)
Foodborne diseases remain substantial and safety of food is an important health, social and economical issue. Food borne illnesses caused by microbial contamination raises concerns to find alternate sources which are safe to human and environmental health. This study was investigated to determine the antibacterial activity of broccoli (Brassica oleracea L. var. italica). Various solvent extracts of broccoli were prepared and analyzed for their phytoconstituents. A total of six food borne bacteria viz., Bacillus cereus ATCC 10876, Bacillus subtilis ATCC 6633, Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 8739, Salmonella typhimurium MTCC 3224 and Shigella flexneri ATCC 12022 were tested against the broccoli extracts. Minimum inhibitory concentration (MIC) values of 10 - 320 µg ml-1 were recorded against most of the pathogens with acetone and methanol as the potential extracts. B. subtilis ATCC 6633 (15.4 mm) and Bacillus cereus ATCC 10876 (16.3 mm) were found to be the most sensitive organisms among the pathogens tested.
Keywords: Broccoli, food borne pathogens, antibacterial,